14. PROSPECTS FOR THE DEVELOPMENT OF COMMUNICATION AND TRANSPORT SYSTEMS IN UZBEKISTAN - Salimov Bakhriddin Lutfullaevich. Muxtorov Ibodullo Murodillaevich (Innovative technologies in construction Scientific Journal, 2023)
The article analyzes the fact that the creation of society, which is the fruit of social relations, saved people from primitive times, and that the creation of society played an important role in the strengthening of the position of communication in people’s lifestyle, the emergence of the need for transportation and its further development.